Advances in the Global Distribution, Chemical Constituents, and Pharmacology of Hippocampus, a Traditional Marine Chinese Medicine - Cui, Xinhai; Zhao, Xiangfeng; Li, Jintong; Li, Ziwei; Ren, Xia; Zhao, Yangang; Fu, Xianjun; Li, Xiuxue (Frontiers in Marine Science, 2021)
Hippocampus, a precious traditional marine Chinese medicine resource, has been used to warm and tonify kidney yang on clinic for a long history in China. Modern pharmacological studies have shown that its active ingredients possessed a wide range of pharmacological activities, with effects in the kidney, as well as anti-inflammatory, antioxidant, anti-tumor, neuroprotection, etc. The research progress on resource distribution, active ingredients, pharmacological activities and clinical application of Hippocampus were systematically analyzed and summarized. First, species and world distribution of Hippocampus were sorted out to clarify the existing resources, the result show that 44 species of Hippocampus have been found in 159 countries and regions in the world. Then, based on analysis of sixteen kinds of active ingredients and extraction methods, this review revealed the relationship between the ingredients-extractions-pharmacological activities of Hippocampus. This review may provide a foundation for further research on potential active ingredients and mechanisms of Hippocampus. Finally, research status of traditional prescriptions containing Hippocampus were presented. Above all this result implied that researches on Hippocampus was still in infancy, the mechanism and material basis of its efficacy was not yet clear. This review was expected to provide detailed information for further study of Hippocampus.